Analisis Data Lifting Migas Menggunakan Metode C4.5 Pada Asosiasi Daerah Penghasil Migas - Ahmad Husain (Universitas Indraprasta PGRI Jakarta, 2018)
One of ADPM's Work programs every year is to provide a data analysis of oil and gas lifting to all members of ADPM. The purpose of this research is to make the regional oil and gas producers can take decisions in determining the regional revenue from the sale of oil and gas in a timely and efficient manner. In the process of making decision-making required raw data to be processed so that will produce an appropriate decision. The first step that must be done is entering data member of producing region, its production data and data of oil and gas lifting year 2014-2015 by using Microsoft Excel which will be used as raw data in RapidMiner data processing application. The second step is selecting data that is not needed in data processing in RapidMiner. From the data that has been selected that will be used as training data, training data will be made some classification required for the process of data management to get accurate and precise results, so that the Region Oil and Gas Producers can determine the realization of lifting with precise and accurate.